Five minutes a day to an upgraded therapy practice : transtheoretical tips to help you make the most of each session - Ellis, Stephanie (Psychologist) (New York, NY : Routledge, 2021)
"Five Minutes a Day to an Upgraded Therapy Practice is a compilation of short, useful suggestions based on classic theory, current research, and wisdom gathered over fifteen years of clinical practice, supervision, and graduate teaching in psychology and counseling. Chapters include highly practical upgrades on standard therapy techniques and ideas for continual therapist development (that respect the busy life of the mental health professional!). The book is made up of ten sections, each with ten short chapters, each readable in under five minutes. It is an indispensable resource for practicing mental health clinicians, including counselors, clinical social workers, psychologists, and other helpers, as well as advanced students in counseling or similar graduate programs"--
How does the "talking cure" cure? (The infrastructure of therapy) -- We've got to walk before we dance (revisiting & revamping basic skills) -- Watch your mouth! (Therapeutic language) -- It's actually not magic (exploration of change processes) -- What we can get away with (and what we can, but shouldn't) -- Deepening knowledge (without a lot of spare time) -- Ethics for practice (not just the school stuff) -- It's a lifelong journey (real professional development) -- We are not immune (common cognitive distortions) -- We can only be who we are (self-as-therapist) -- Parting words.
Keywords: Psychotherapy; PSYCHOLOGY / Psychotherapy / Counseling; EDUCATION / Counseling / General